Self-Assessment: One of Ways Attaining Students’ Target Language in Autonomous Learning - Sungkawati Kardi Wahyuningsih (Asosiasi Dosen Perguruan Tinggi Islam, 2017)
This paper introduces the steps in developing students’ self-assessment in autonomous learning. Self-assessment is used as reflection students’ knowledge and understanding and also to motivate students to learning independently. Self-assessment will help students to attain their target language by learning autonomously. There are five ways in developing students’ self assessment. They are (1) Conduct an honest review of the learning process; (2) Set the goals regarding to the learning process for a period; (3) Breaks the goals into the smaller competence for every learning time; (4) Refer back to the self-assessment to ensure that the goals are in line to improving the language skills; and (5) Conduct another self-assessment in next period to get an idea of how your goals are progressing and whether they have been an effective way to improve the language skills.